Rezim Standar Industri Pariwisata dan Paradoks Pembangunan Desa Wisata di Indonesia: Pengalaman Desa Mangunan - Gama Abisono Nasution, Fatih (Department of Political Sciences, Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2021)
The structural perspective explains well the paradox of development through the phenomenon of democratization in the trap of electoralism that does not change the inequality of power relations. This article moves in a different sense by offering the concept of governmentality in exploring the paradox of development. However, this study does not reject the argument that the paradoxical failure of development stems from the development mode that results in the depoliticization of development. The author deepens this argument by examining microscopically the types of power that work. More specifically, this study discusses the question of how the existing regime of knowledge about development produces paradoxical symptoms. Departing from the case of Mangunan Village, Bantul Regency, the findings in this study indicate that tourism development which was built in the name of a program to improve the welfare of the citizens in fact only serves the growth of the tourism industry. This can be seen from the knowledge regime that underlies the existence of the programs being carried out, namely encouraging the growth of the tourism industry that meets tourism business standards. This kind of knowledge regime is only possible for business actors who have access and resources to meet various tourism industry standards. Meanwhile, residents with limited resource capacity cannot meet various standards. In short, this kind of knowledge regime actually contributes to widening the gap in economic inequality between citizens.